Thailand and the Southeast Asian Networks of The Vietnamese Revolution, 1885-1954, 1st Edition - Goscha, Christopher E. (Routledge, 2020)
Christopher Goscha resituates the Vietnamese revolution and war against the French into its Asian context. Breaking with nationalist and colonial historiographies which have largely locked Vietnam into 'Indochinese' or 'Nation-state' straightjackets, Goscha takes Thailand as his point of departure for exploring how the Vietnamese revolution was intimately linked to Asia between the birth of the 'Save the King Movement' in 1885 and the Battle of Dien Bien Phu in 1954.